Evaluasi Capaian Program Supervisi Pengajaran untuk Optimalisasi Praktik Pembelajaran di SMAN 5 Banjarmasin - Sulis Anggraeni; Besse Maryani; Agus Syukran; Sulistiyana Sulistiyana; Metroyadi Metroyadi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study aims to evaluate the implementation of the instructional supervision program at SMAN 5 Banjarmasin by examining its execution quality, feedback effectiveness, and the extent to which follow-up actions support improvements in teachers’ classroom practices. Data were collected through interviews with the principal, teachers, and supervisors, classroom observations, and an analysis of supervision documents. The findings indicate that supervision has contributed to enhancing teacher reflection and lesson planning; however, it has not consistently led to sustained changes in teaching practices. The supervision process remains largely administrative, offering limited opportunities for pedagogical guidance, deep reflection, and collaborative problem-solving. Differences in stakeholders’ perceptions and irregular observation schedules further reduce the consistency and quality of supervision. Moreover, follow-up actions after supervision are insufficiently structured, resulting in only a small proportion of recommendations being implemented by teachers. These findings align with existing literature emphasizing the importance of dialogic supervision, ongoing coaching, and systematic monitoring to ensure that professional development translates into classroom practice. The study recommends strengthening supervisors’ competencies, utilizing more comprehensive observation instruments, and adopting evaluation models such as CIPP to ensure that supervision functions as a professional learning process rather than a procedural requirement. With these improvements, the supervision program is expected to play a more effective role in enhancing teaching quality and supporting continuous teacher development. Keywords: CIPP, program evaluation, teaching supervision, teacher professionalism Abstrak: Penelitian ini bertujuan mengevaluasi pelaksanaan program supervisi pengajaran di SMAN 5 Banjarmasin dengan menelaah kualitas implementasi, efektivitas umpan balik, serta keberlanjutan tindak lanjut supervisi terhadap peningkatan praktik pembelajaran guru. Data dikumpulkan melalui wawancara dengan kepala sekolah, guru, dan pengawas; observasi kelas; serta analisis dokumen supervisi. Hasil penelitian menunjukkan bahwa supervisi telah memberikan kontribusi terhadap peningkatan refleksi guru dan perencanaan pembelajaran, namun belum sepenuhnya menghasilkan perubahan mengajar yang konsisten. Pelaksanaan supervisi masih berfokus pada aspek administratif sehingga ruang pembinaan pedagogik, seperti diskusi mendalam dan refleksi terarah, belum berjalan optimal. Variasi persepsi antar-pemangku kepentingan dan ketidakteraturan observasi juga menyebabkan mutu supervisi tidak merata. Selain itu, tindak lanjut supervisi belum terstruktur dan hanya sebagian kecil rekomendasi yang benar-benar diterapkan oleh guru. Temuan ini diperkuat oleh literatur mengenai pentingnya supervisi dialogis, coaching berkelanjutan, serta mekanisme pemantauan yang konsisten untuk memastikan transfer pengetahuan ke praktik pembelajaran. Studi ini merekomendasikan penguatan kapasitas supervisor, penggunaan instrumen observasi yang lebih komprehensif, serta penerapan model evaluasi seperti CIPP untuk memastikan supervisi berjalan sebagai proses pembinaan profesional, bukan sekadar pemenuhan administrasi. Dengan penguatan tersebut, supervisi diharapkan dapat berperan lebih efektif dalam meningkatkan kualitas pembelajaran dan kinerja guru secara berkelanjutan. Kata kunci: CIPP, evaluasi program, supervisi pengajaran, profesionalisme guru